Early-life cognitively stimulating activities and late-life cognitive function in the St. Louis Baby Tooth Later Life Health Study - Andrea L. Roberts; Xinye Qiu; Kaleigh A. McAlaine; Laura T. Germine; Ran S. Rotem; Marc G. Weisskopf (Scientific Reports)
Abstract Childhood cognitively stimulating activities have been associated with higher cognitive function in late life. Whether activities in early or late childhood are more salient, and whether activities are associated with specific cognitive domains is unknown. Participants retrospectively reported cognitively stimulating activities at ages 6, 12, and 18 years. 4,198 participants were aged 55 to 77 years at cognitive testing. Six tasks measured overall cognitive function, processing speed, visual short-term memory, attention, cognitive control, episodic memory, working memory, perception, vocabulary, and verbal reasoning. Cognitively stimulating activities across childhood were associated with higher cognitive scores (highest versus lowest quartile, beta = 0.18 SD, 95% CI = 0.12, 0.23). In models adjusted for activities at each age, only age 18 activities were associated with overall cognition. The association of activities with cognitive function was strongly positive at the lowest levels of activities, with little association at middle and high levels of activities. A test of crystalized intelligence was most strongly associated with activities; tests assessing processing speed, visual short-term memory, visual working memory, and sustained attention were least associated. If the associations we found are causal, increasing cognitively stimulating activities in the late teen years among those with very few activities may benefit late life cognitive health.